Structure et diversité des peuplements arborescents des sols hydromorpphes et terres fermes de Yoko en province de la Tshopo, RD Congo - LISIKO BOYEMBA; LISINGO WA LISINGO; BOYEMBA BOSELA.; KOMBE LIBENGE (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The floristic structure and the specific diversity are induced by the edaphic factor and vary according to scale of investigation as well as the heterogeneity of the substrate. The present study was carrieout in Yoko (forest reserve), to evaluate and compare the diametric structure and the floristic diversity of the forests of the Congolese central basin. The sampling unit is a 300m x 150m L-shaped device. Eight 50m x 50m plots (0.25 ha) were delineated in each stand. In these plots, we surveyed and measured the circumference (at 1.30 m from the ground) of all trees at dhp ≥ at 10 cm. We show that the two stands are different and have significant variations in their diametric structure, richness & specific diversity, and floristic composition. The results obtained can be summed up as follows: (i) diametric structure (λ² = 19.2; dl = 7, p <0.01). The difference is significant between the diametric structures of the studied stands (ii) wealth and specific diversity (t = -3.388, dl = 14, p <0.01). The difference is very significant between the studied stands. And the alpha diversity index of Fisher, α = 30.2 and α = 44 respectively of the mainland stands and those of hydromorphic soils. For any identical inventoried surface, the number of species is higher in the mainland stand for areas less than 1 ha, and lower than in the hydromorphous soil stand for areas greater than 1 ha.